2005
DOI: 10.7202/705355ar
|View full text |Cite
|
Sign up to set email alerts
|

Les herbicides inhibateurs du photosystème II, effets sur les communautés algales et leur dynamique

Abstract: Nous présentons une revue bibliographique à propos des effets des herbicides inhibiteurs du Photosystème II (PS II) sur les communautés algales. Ces herbicides sont abondamment utilisés dans les pratiques phytosanitaires. Ils sont susceptibles de contaminer les milieux aquatiques et, étant donné leur mode d'action inhibitrice de la photosynthèse, ils peuvent agir directement sur les algues. De nombreuses études ont été réalisées afin d'évaluer l'impact des contaminations par ces herbicides sur les microphytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 99 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…The pigment fingerprint profiles were also modified by the herbicide application, which may indicate that there were shifts in microalgal community composition. Microalgae species have different pigments, and the pigment composition of a given species may vary according to its physiological state, especially if herbicides induce conditions of stress (Bérard and Pelte, 1999). That said, pigment profiling of soil or water samples remains a suitable and widely used approach for describing phytoplankton community structure (Zapata et al, 2000) and for examining how microalgal community composition responds to herbicides (Dorigo et al, 2004; Joly et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The pigment fingerprint profiles were also modified by the herbicide application, which may indicate that there were shifts in microalgal community composition. Microalgae species have different pigments, and the pigment composition of a given species may vary according to its physiological state, especially if herbicides induce conditions of stress (Bérard and Pelte, 1999). That said, pigment profiling of soil or water samples remains a suitable and widely used approach for describing phytoplankton community structure (Zapata et al, 2000) and for examining how microalgal community composition responds to herbicides (Dorigo et al, 2004; Joly et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…6) have been shown to significantly inhibit PSII by acting specifically at several sites completely separate from the target site of diuron (Fig. 15) (3-(3,4-34 dichlorophenyl)-1,1-dimethylurea), a herbicide known for its PSII inhibition action [176] and which acts mainly in competition with plastoquinone [177]. Through this study, the authors demonstrated that in the short term fischerellins inactivate the reaction centers of the PSII and, in the long term, deconstruct the PSII, thus preventing energy transfer via the reaction center.…”
Section: Microalgae Herbicidal Compounds For Target-based Approachmentioning
confidence: 99%